2008
DOI: 10.1021/np800585c
|View full text |Cite
|
Sign up to set email alerts
|

LCMS and GCMS for the Screening of Alkaloids in Natural and in Vitro Extracts of Leucojum aestivum

Abstract: HPLC coupled to a mass spectrometer (MS) was used for the analysis of galanthamine and lycorine in natural extracts of Leucojum aestivum and in their in vitro cultures grown with a precursor (ACC), inhibitors (AgNO(3), STS), or an absorber (KMnO(4)) of ethylene. The maximum galanthamine (0.002%) and lycorine (0.02%) concentrations in tissue cultures were obtained in the presence of KMnO(4). GCMS was used to investigate underivatized alkaloid mixtures from L. aestivum. Seven alkaloids were identified in in vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 34 publications
(62 reference statements)
2
52
0
Order By: Relevance
“…Several other compounds were also detected in in vitro extracts only, but they could not be identified. Dramatic variations in the profile of alkaloids were observed previously in tissue cultures of Leucojum aestivum, depending upon the balance of growth substances and the state of differentiation [11]. The positive effect of 2,4-D combined with BA was also shown in berberine production by in vitro culture of Coscinium fenestratum [46].…”
Section: Effect Of Auxins On Alkaloid Profile In Callus Cultures Of Lmentioning
confidence: 77%
See 3 more Smart Citations
“…Several other compounds were also detected in in vitro extracts only, but they could not be identified. Dramatic variations in the profile of alkaloids were observed previously in tissue cultures of Leucojum aestivum, depending upon the balance of growth substances and the state of differentiation [11]. The positive effect of 2,4-D combined with BA was also shown in berberine production by in vitro culture of Coscinium fenestratum [46].…”
Section: Effect Of Auxins On Alkaloid Profile In Callus Cultures Of Lmentioning
confidence: 77%
“…Leaves were isolated from Leucojum aestivum L. 60 bulbs chilled for 12 weeks at 5ºC were surface-sterilized as previously described by Ptak et al [11]. In vivo bulbs were used for both in vitro culture establishment and chemical analysis.…”
Section: Plant Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Inhibitors of ethylene biosynthesis increased paclitaxel production in cell culture of Taxus (Tabata 2004). Our preliminary results (Ptak et al 2009) showed that the control of ethylene production can be important for somatic embryogenesis and for alkaloid synthesis in L. aestivum culture. A stimulatory effect of an ethylene inhibitor (STS) and of KMnO 4 was observed on embryogenic callus induction and alkaloid production.…”
Section: Introductionmentioning
confidence: 65%